A Comparison of the Results of Two Different Double-Row Repair Techniques in Arthroscopic Repair of Rotator Cuff Tears - Gökhan Ünlü; Mehmet Faruk Çatma; Ahmet Burak Satılmış; Tolgahan Cengiz; Serhan Ünlü; Mustafa Erdem; Önder Ersan (Medicina)
Background and Objectives: Shoulder pain, mainly involving rotator cuff tears, is a common type of musculoskeletal pain that significantly impairs quality of life. Arthroscopic rotator cuff repair has become the gold standard for treating symptomatic, full-thickness rotator cuff tears. Double-row repair techniques are widely used because of their superior fixation and healing results. However, fewer implants may reduce treatment costs and raise questions about the impact on clinical outcomes and re-tear rates. This study compares the functional outcomes and re-tear rates of two transosseous-like double-row repair techniques: one anchor and one push lock (Group 1), and two anchors and two push locks (Group 2). Materials and Methods: A prospective, randomized, single-blind study was conducted on 53 patients undergoing arthroscopic repair for crescent-shaped rotator cuff tears (3–5 cm). Before surgery and 24 months after surgery, patients were evaluated for shoulder function using Constant–Murley scores and shoulder abduction angles. MRI was used to assess re-tear rates. Results: Both groups showed significant postoperative improvement in Constant scores (Group 1: 84.1; Group 2: 84.0; p > 0.05). Re-tear rates were slightly higher in Group 1 (23.1%) than in Group 2 (18.5%), but this was not statistically significant (p > 0.05). Shoulder abduction angles improved similarly between groups, with no significant difference in outcome. Despite higher costs and longer operative times, the two-anchor technique provided more stable fixation, but its functional outcomes were comparable to the single-anchor method. Conclusions: Using fewer implants in a double-row repair provides comparable functional outcomes and re-tear rates, and offers surgeons a cost-effective alternative, especially at the beginning of their learning curve. However, the two-anchor technique may be more beneficial in cases requiring improved mechanical stability. These findings provide valuable information to balance cost and effectiveness in rotator cuff repair.